Penambaham Tepung Daun Kelor Dalam Pembuatan Mie Sebagai Sumber Gizi Dengan Penambahan Ekstrak Umbi Wortel Sebagai Pengawet Alami - RAHAYU, DARSITI; , Dra. Aminah Asngad, M.Si (2016)
Wet noodles is a food that is favored by the public, but the nutrient content and storability of wet noodles are relatively low. The purpose of this research is to increase the protein content of wet noodles with the addition of moringa leaf powder and the addition of carrot extract to increase the shelf life of wet noodles. This research make a method Completely Randomized Design (LAP) with two factors, the first factor : variation of wheat flour : flour of moringa leaves 97 g: 3 g (M1), 95 g: 5 g (M2), 93 g: 7 g (M3) and secend factor : variation extract carrots 3 ml (W1), 5 ml (W2) and 7 ml (W3). Data analysis using descriptive qualitative. The results showed highest protein content in M3W1 (3 ml carrot extract with wheat flour 93 g flour Moringa leaves 7 g) is 4.7635%. The shelf life of wet noodles longest in M3W3 (carrot extract 7ml with wheat flour 93 g flour Moringa leaves 7g) which is 19 days of storage in a refrigerator at a temperature of ± 8 0C. Organoleptic M1W1, M1W2, M1W3 with faded yellow color, scent is not pungent and little sting, chewy texture, can be accepted by society. Conclusion suggests the addition of moringa leaf powder and carrot extracts influenced the protein content, storability and orgaoleptik wet noodle.